Boosting the oxygen evolution activity of copper foam containing trace Ni by intentionally supplementing Fe and forming nanowires in anodization. (20th December 2020) - Anantharaj, Sengeni; Sugime, Hisashi; Chen, Bozhi; Akagi, Natsuho; Noda, Suguru
Highlights: Poorly OER active Cu foam with trace Ni was made into a highly active catalyst by anodization. Intentionally supplementing Fe during anodization further improved the OER activity. Pure Cu containing no Ni did not show such enhancement. Cu foam containing Ni formed structurally interesting Cu(OH)2-CuO nanowires while anodizing in the presence of Fe. As a combined effect, η 50 was lowered by 153 mV after anodization in Fe added KOH. Abstract: Oxygen evolution reaction (OER) is the bottleneck for realizing energy-efficient hydrogen production through water electrolysis in both acid and alkali. Alkaline OER electrocatalyzed by Ni and Co hydroxides are well known which showed unexpected enhancement with the addition of Fe. We found that the commercially procured Cu foam containing trace amount of Ni ( 1.5 wt.%) upon anodization formed Cu(OH)2 CuO nanowires with conceivable formation of Ni(OH)2 and experienced a notable enhancement in its OER activity. When sufficient amount of Fe was intentionally supplemented during anodization, OER activity of the same was further improved. Specifically, as a combined result of anodization in KOH and in Fe supplemented KOH, overpotential at 50 mA cm −2 was lowered by 153 mV. Such an activation also improved the kinetics of OER by lowering the Tafel slope by 100 mV dec −1 . With these, it has been shown here that a moderately active OER catalyst i.e., Cu(OH)2 CuO/Cu formed upon the anodization of Cu foam can be turned into a highly active catalyst just by utilizing the trace Ni that it already contains and intentionally supplementing sufficient amount of Fe. Graphical abstract: A Cu foam that contains a trace amount of Ni upon anodization in alkali with sufficiently supplemented Fe resulted in humongous enhancement in OER activity. Image, graphical abstract